Multidimensional Sevilla Carpets associated with P systems - Miguel A. Gutiérrez-Naranjo; Mario J. Pérez-Jiménez; Agustín Riscos-Núñez (Fénix Editora, 2005)
In this paper we address the problem of describing the complexity of the evolution of a P system. This is especially difficult in the case of P systems where the number of membranes increases along the computation, via division or creation of membranes. In these cases the number of steps of a computation is not sufficient to evaluate the complexity. Sevilla Carpets were introduced in [1], and they describe the space-time complexity of P systems. Based on them, we define a four-dimensional manifold which can be used to compare evolutions of P systems.